Real-time SAR-CORDIC Algorithm and Application in Signal Generation and Scene Simulation - Wenda, Zhao; DeCheng, Chen; Song, Han; Yanfei, Wang (2020 IEEE 3rd International Conference on Electronics Technology (ICET), 2020)
A coordinate rotation digital computation (CORDIC) based synthetic aperture radar (SAR) signal generation method is proposed to replace the traditional ROM-based direct digital synthesis (DDS) architecture in large scene electromagnetical echo simulation application. Considering the restriction and low-efficiency of general mathematical calculation, we find the CORDIC algorithm can maintain high precision result in transcedental function calculation and fast speed in reachable way. Both senarios in square root and trigonometic computation are analyzed. A combined CORDIC-I, II, III structure is applied in SAR signal generation named SAR-CORDIC, meanwhile, it is shown that this method can operate in wide range of input and sustain convergence. Relevant signal processing principles and procedures are also discussed in our works. We believe this method beyond its signal form can achieve resourceful accomplishment in future FPGA or ASIC signal processing application.